Performances économiques des Etats-Unis dans les années nonante - Alain Nyssens; Paul Butzen; Patrick Bisciari (National Bank of Belgium, 2000)
– This article gives a general overview of economic developments in the United States in the nineties and aims to highlight certain structural characteristics underlying them. The performance of the American economy is situated in a longer-term perspective and compared with those of other advanced economies. This article also offers a cautious explanation of the extremely sustained and non-inflationist growth during the second half of the last decade. To this end, three approaches have been used: an analysis of demand determinants; growth accounting; and a "Structural Vector Autoregressive" model to disentangle the contribution of demand and supply factors. Since labour supply appears to have made a substantial contribution to American growth, the article also includes an evaluation of the role layed by demographic factors and the organisation of the labour market in developments in employment and unemployment in the United States, as well as in the eurozone. Special attention is also paid to the imbalances shown by the American economy and, more particularly, to the question of the sustainability of the current deficit.
Keywords: 330; Wirtschaftswachstum; Arbeitsmarkt; Bevölkerungsstruktur; Außenwirtschaftliches Gleichgewicht; USA